Neurochemical Correlates of Captagon and Crystal Methamphetamine Addiction in Iraq: A Focus on Dopamine and Total Protein - Mahmood Atta, Buraq; H. Hassoon, Athraa (Journal of Neonatal Surgery, 2025)
Background: Captagon (Kat) and crystal methamphetamine (crystal) are highly addictive stimulants that are widely used in Iraq. The neurochemical effects of these substances were examined in this study by comparing dopamine and total protein levels in users and a control group. Methods: Blood samples were obtained from thirty control persons, fifty crystal addicts, and fifty Captagon addicts. The dopamine concentration was assessed utilizing an ELISA kit, whereas the determination of total protein levels was conducted using the Biuret method. Statistical analysis compared discrepancies between groups and the effects of age and body mass index (BMI). Results and discussion: Dopamine levels were most significant among Crystal addicts, then those of Captagon addicts, and finally those of the control group. This indicates that dopamine release may have been elevated as a result of drug use. Crystal addicts had the lowest levels of total protein, which was considerably lower than the control group. This may be an indication of dietary deficits brought on by drug usage. The protein levels of captagon addicts did not differ significantly from those of the control group. Variation in the impact of BMI on protein and dopamine levels was seen among the groups. In the lower BMI range (14-18.9), Crystal and control groups exhibited increased dopamine levels, whereas Captagon addicts exhibited comparable levels in both BMI ranges. Protein concentrations were marginally elevated within the lower BMI range in the control group. Age: Regardless of age, crystal users have consistently elevated dopamine levels (15-25 and 26-35). Within the younger age group, captagon addicts exhibited dopamine levels that were higher than the control group but lower than crystal users. Conclusions: Addiction to Crystal and Captagon is correlated with unique modifications in levels of dopamine and protein. Crystal addicts demonstrated the most pronounced increase in dopamine levels and the lowest levels of protein, which may indicate neurochemical and nutritional alterations.